Pengaruh Kesadaran Wajib Pajak Dan Tingkat Pemahaman Wajib Pajak Kendaraan Bermotor Terhadap Kepatuhan Wajib Pajak (Studi Kasus Kantor Samsat Di Kabupaten Lamongan) - Feriza Lucia Islammiyah; Anik Yuliati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The puporse of this study is to determine and test empirically the effect of taxpayer awareness and the level of understanding of motorized vehicle taxpayers on SAMSAT compliance in Lamongan Regency. The research used a quantitative approach, using primary data through questionnaires. The subjects of this study were all motorized vehicle taxpayers in the SAMSAT Office of Lamongan Regency. The sample in this study used non-probability sampling with the slovin formula technique with a total of 100 samples. The analysis technique in this study used multiple linear regression analysis with the help of IMB SPSS Statistics 26 software. The results of this study indicate that (1) Taxpayer awareness has a significant effect on increasing taxpayer compliance. (2) Taxpayer understanding has a significant effect on increasing taxpayer compliance. Keywords : Taxpayer Awareness, Taxpayer Understanding, Taxpayer Compliance